2012
DOI: 10.4304/jltr.3.3.508-517
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between English Self-concept and Language Learning Strategies

Abstract: Abstract-The present study concentrated on the relationship between self-concept and language learning strategies. Participants of the study were 157 students from one University in Shandong, China. Quantitative data was collected through two questionnaires. The first one was the revised Chinese version of self-concept scale modified by Pan (2003) from Marsh's (1992) SQDII. Another inventory based on Oxford' classification system of learning strategies (SILL) was used to assess learner's strategy use. By the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…The first student did it successfully and the second did it less successfully. In addition, the imbalance inhibited the third learner to make any effort [25]. These findings showed that when a group of students have the same level or form of self-concept, the way a student behaves in relation to that self-concept might differ.…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…The first student did it successfully and the second did it less successfully. In addition, the imbalance inhibited the third learner to make any effort [25]. These findings showed that when a group of students have the same level or form of self-concept, the way a student behaves in relation to that self-concept might differ.…”
Section: Literature Reviewmentioning
confidence: 91%
“…This means that its relation to the factor studied was treated as a straightforward phenomenon and the possibility that multiple variables might take place in its formation was ignored. A study by Chen [25] tried to fill this gap by using a qualitative case study design in studying the complexity of self-concept system. Studying three EFL students, Chen [25] concluded that the imbalance between general self-concept and specific self-concept (for example, a student believes that he is good in English, but not in pronunciation) can result in different outcome.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By pass of time, novel experiences accumulate which are influenced by pas experiences. As individuals grow older they may feel more need to protect their fragile ego (Du, 2012). The results of Jing's (2006) study revealed that English self-concept also impacts on the application of learning strategies.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Here again, across various grade levels and educational tracks the female students consistently displayed better outcomes in learning English as a foreign language than male students (Hartig & Jude, 2008;Lehmann, Gänsfuß & Husfeldt, 2011;Nikolova, 2011;Nikolova & Ivanov, 2010;Schilling, Sparfeldt & Rost, 2006;Winkelmann & Groeneveld, 2010;Zaunbauer, Retelsdorf & Möller, 2009). However, whilst some studies reported significant self-concept differences favoring the female language learners (Dörnyei & Clément, 2001;Du, 2012;Heinzmann, 2009;Henry, 2009;Schilling, Sparfeldt & Rost, 2006), other studies failed to demonstrate any gender differences in the L2 self-concept (Daniels, 2008;Helmke, Schrader, Wagner, Nold & Schröder, 2008;Holder, 2005;Krätschmar, 2010;Kurman, 2004;MacIntyre, Baker, Clément & Donovan, 2002;Skaalvik & Skaalvik, 2004;Zaunbauer, Retelsdorf & Möller, 2009). …”
Section: Introductionmentioning
confidence: 99%